PENGGUNAAN MULTIMEDIA INTERAKTIF DAN AUGMENTED REALITY UNTUK MENINGKATKAN HASIL BELAJAR SISTEM KELISTRIKAN - Nofiandri, Ernal; Efrinaldi, Efrinaldi (Universitas Negeri Padang, 2021)
This Best Practice aims to describe the use of interactive multimedia and augmented reality that can increase student interest/motivation in the learning process so that the achievement of learning outcomes is better and to determine the increase in understanding of the subject matter and have a positive impact on the use of information technology tools such as computers. and smartphones owned by students. This best practice uses problem solving methods and strategies. With the use of interactive multimedia and augmented reality in improving student learning outcomes, real and significant results are obtained that there is an increase in student interest/motivation in learning and an increase in student learning outcomes in light vehicle electrical system competencies for students of class XI Automotive Light Vehicle Engineering at SMK Negeri 1 Calang.